2018
DOI: 10.1111/ter.12364
|View full text |Cite
|
Sign up to set email alerts
|

Detrital zircon U–Pb geochronology of a Cenozoic foreland basin in Northeast India: Implications for zircon provenance during the collision of the Indian and Asian plates

Abstract: Geochronology is useful for understanding provenance, and while it has been applied to the central and western Himalaya, very little data are available in the eastern Himalaya. This study presents detrital zircon U-Pb ages from the late Palaeocene-Eocene Yinkiong Group in NE India. The samples are from the late Palaeocene to early Eocene Lower Yinkiong Formation, and the Upper Yinkiong Formation deposited during the early to mid-Eocene within the Himalayan foreland basin. The U-Pb ages of the detrital zircon w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 43 publications
(57 reference statements)
0
14
0
Order By: Relevance
“…(2017) proposed a diachronous collision model to explain the broad range of collision ages. According to our statistics (Table in the supporting information), several studies from the past 2 decades propose that the India‐Asia collision occurred during the early Paleogene (65–50 Ma) and imply a diachronous collision that first occurred in the central Himalaya at 65–59 Ma (e.g., L. Ding et al., 2005; Hu et al., 2015; L. Ma et al., 2017; Orme et al., 2015; Wu et al., 2014) and then progressed westwards initiating at 56–54 Ma in the NW Himalaya (e.g., Clementz et al., 2011; L. Ding, Qasim, et al., 2016; Green et al., 2008; Najman et al., 2016; Qasim et al., 2018), and eastwards where collision initiated at ∼50 Ma (e.g., Baral et al., 2018; H. Ding, Zhang, et al., 2016; B. Zhu et al., 2005). Meanwhile, Early Cenozoic continental sediments deposited contemporaneously or soon after the onset of India‐Asia collision provide an obvious target for gaining insight into growth of the Tibetan Plateau (Studnicki‐Gizbert et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(2017) proposed a diachronous collision model to explain the broad range of collision ages. According to our statistics (Table in the supporting information), several studies from the past 2 decades propose that the India‐Asia collision occurred during the early Paleogene (65–50 Ma) and imply a diachronous collision that first occurred in the central Himalaya at 65–59 Ma (e.g., L. Ding et al., 2005; Hu et al., 2015; L. Ma et al., 2017; Orme et al., 2015; Wu et al., 2014) and then progressed westwards initiating at 56–54 Ma in the NW Himalaya (e.g., Clementz et al., 2011; L. Ding, Qasim, et al., 2016; Green et al., 2008; Najman et al., 2016; Qasim et al., 2018), and eastwards where collision initiated at ∼50 Ma (e.g., Baral et al., 2018; H. Ding, Zhang, et al., 2016; B. Zhu et al., 2005). Meanwhile, Early Cenozoic continental sediments deposited contemporaneously or soon after the onset of India‐Asia collision provide an obvious target for gaining insight into growth of the Tibetan Plateau (Studnicki‐Gizbert et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Since ∼50 Ma, with India‐Asia collision occurring in the eastern Himalaya (Baral et al., 2018; H. Ding, Zhang, et al., 2016; Uddin et al., 2007; B. Zhu et al., 2005), the southeast Tibetan Plateau came into rapid ascent with enhanced crustal deformation in Eocene (e.g., DePaolo et al., 2019; Hoke et al., 2014; C. Wang et al., 2014), followed by the activation of thrust faults that caused a basin‐scale syncline (Figure 8b). Meanwhile, volcanic eruptions became more frequent and a potassium‐rich magmatic belt formed within and around Gonjo Basin at 51–32 Ma (e.g., Chung et al., 1998; Z. Li et al., 2004; Roger et al., 2000; Spurlin et al., 2005; J. Wang et al., 2001) (Figure and Table in the supporting information).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2436, 2136, 2013 Ma) of the inherited zircons. Baral et al (2019) reported the U-Pb ages of detrital magmatic zircons from the late Palaeocene to early Eocene Lower Yinkiong Formation, NE Himalaya which mostly cluster between Cambrian and Archaean, resembling cratonic and early Himalayan Thrust Belt affinity. Early to Mid-Eocene Upper Yinkiong Formation record Cenozoic magmatic zircons having Asian as well as Himalayan Thrust Belt resemblance.…”
mentioning
confidence: 99%